EFFECT OF CHEWING GUM ON COGNITION AND BEHAVIOURAL ATTRIBUTES - Haq, Inam ul; Saleem, Muhammad Amer; Ansari, Ali Raza; Hassan, Hamza; Yousaf, Anum (Pakistan Journal of Physiology, 2016)
Background: Chewing gum has multidimensional effects on the body that work in harmony to improve one’s abilities. The present study was aimed to focus at the authenticity of the myth that chewing gum reduces stress, elevates mood and increases concentration. Methodology: This descriptive cross-sectional survey and observational analytic study was carried at Rawalpindi Medical College, Rawalpindi over a period of 3 weeks. A total of 200 subjects participated in the study. They filled in their demographic details and self-rated their stress levels in various situations. The group was equally divided into a control and a study group. All the participants were subjected to a mental arithmetic test. The participants of the study group were provided with a gum during their examination. A comparison of the marks scored was done. Results: Out of the entire group only 13.3% were non-chewers whereas 50% replied that they chewed gum ‘sometimes’. Majority of the people felt mild, moderate and severe stress in general, while in college and during examination respectively. A large number of subjects chewed gum for the reason that it makes them feel elated (43.3%). In the mental arithmetic test, the non-chewer group scored more than the chewer group with a highly significant statistical difference (p=0.001). Conclusion: Chewing gum has no or minimal role in reducing stress. However, as it cherishes ones’ mood, it can be chewed to get rid of the acute anxiety states faced during various stressful conditions. Nevertheless, the study strongly denounces the concept that chewing gum enhances ones attention and cognition. Pak J Physiol 2016;12(1):22–5